The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.foodchem.2015.01.098
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and kinetics of degradation of deoxynivalenol, deoxynivalenol conjugates and ochratoxin A during baking of wheat bakery products

Abstract: The stability of deoxynivalenol (DON), deoxynivalenol-3-glucoside (DON-3-glucoside), 3-acetyldeoxynivalenol (3-ADON), 15-acetyldeoxynivalenol (15-ADON), de-epoxy-deoxynivalenol (DOM-1) and ochratoxin A (OTA) during thermal processing has been studied. Baking temperature, time and initial mycotoxin concentration in the raw materials were assayed as factors. An improved UPLC-MS/MS method to detect DON, DON-3-glucoside, 3-ADON, 15-ADON and DOM-1 in wheat baked products was developed in the present assay. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 40 publications
(70 reference statements)
4
56
1
2
Order By: Relevance
“…Our results were in accordance with previous studies (Milani & Maleki, ; Pacin et al., ; Scudamore, Hazel, Patel, & Scriven, ; Vidal et al., ). The mean reduction in DON between flour and products was 42.3% for French bread and 58.3% for Vienna bread (Pacin et al., ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results were in accordance with previous studies (Milani & Maleki, ; Pacin et al., ; Scudamore, Hazel, Patel, & Scriven, ; Vidal et al., ). The mean reduction in DON between flour and products was 42.3% for French bread and 58.3% for Vienna bread (Pacin et al., ).…”
Section: Discussionsupporting
confidence: 94%
“…The main factors involved in diminishing DON content during bread making process are temperature, time, loaf size, ingredients, and experimental scale (industrial/laboratorial) (Vidal et al., , ). In our study, the DON reduction during the baking process (180°C for 35 min) could be explained by the small size of loaves (100 g), which favored temperature distribution through the inner layers and consequently affected the DON stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of DON reduced by cleaning varied from 7% to 50% (effect of cleaning, sorting, and milling in wheat mycotoxin content). In addition, milling, pearling, and dehulling have effectively reduced DON (Vidal, Marín, Morales, Ramos, & Sanchis, 2014; Vidal, Morales, Sanchis, Ramos, & Marín, 2014; Vidal, Sanchis, Ramos, & Marín, 2015, 2016; Suman & Generotti, 2015). Milling is a process of crushing grain into flour.…”
Section: Fate Of Don During Food Processingmentioning
confidence: 99%
“…Ochratoxin A (OTA) is a mycotoxin with a high nephrotoxicity potential, besides showing hepatotoxicity, teratogenicity, carcinogenicity, cytotoxicity, neurotoxicity are detected in different foods such as coffee (Batista et al, 2009;Casal et al, 2014), grain, like wheat and maize and their derivatives (Juan et al, 2008;Gang et al, 2014;Al-Hadithi et al, 2015), wine (Terra et al, 2013;Giovannoli et al, 2014), powdered guarana (Martin et al, 2014), among others (Obanos et al, 2005;Vidal et al, 2015, Lippolis et al, 2014Pacheco et al, 2015;Marino et al, 2014). At first, it was believed that OTA was produced only by Aspergillus ochraceus and circumdatirelated species, as well as Penicillium verrucosum, though these species are not considered the main OTA sources in some food because OTA may also be produced naturally by Aspergillus carbonarius (Van der Merwe et al, 1965;Horie, 1995, Lund andFrisvad, 2003;Schabo et al, 2015;Kogkaki et al, 2015), since 75-100% of the isolates were found to be ochratoxigenic (Romero et al, 2005).…”
Section: Introductionmentioning
confidence: 99%